Systematic Literature Review On Asymmetric Decentralization - muluk, `mujibur rahman khairul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
The purpose of this study is to map the latest developments on the asymmetric decentralization concept. The increasing use of this concept today is not accompanied by the availability of adequate literature. This mapping is useful to trigger further research as well as to guide the application of the concept in practice. By using systematic literature review on the Proquest database in the last ten years: 2010-2019, important up-to-date information is obtained. The results of this research indicated that there were small number of research on asymmetric decentralization concept that exist. Furthermore, this research also presented the distribution of the research areas. In addition, this research showed the development of the meaning of asymmetric decentralization as well as mapping the scope and content of the developing study. This research also showed the various factors that influenced the effectiveness of asymmetric decentralization, described the impact of the application of this concept in various countries, provided suggestions for further research that would be useful for the development of research on asymmetric decentralization in the future, presented several interesting issues that were useful for further research, and produced an asymmetric decentralization framework